Recruitment of GABAA receptors and fearfulness in chicks: Modulation by systemic insulin and/or epinephrine - Cid, Mariana Paula (2013)
One-day-old chicks were individually assessed on their latency to peck pebbles, and categorized as low latency (LL) or high latency (HL) according to fear. Interactions between acute stress and systemic insulin and epinephrine on GABAA receptor density in the forebrain were studied. At 10 days of life, LL and HL chicks were intraperitoneally injected with insulin, epinephrine or saline, and immediately after stressed by partial water immersion for 15 min and killed by decapitation. Forebrains were dissected and the GABAA receptor density was measured ex vivo by the 3[H]-flunitrazepam binding assay in synaptosomes. In non-stressed chicks, insulin (non-hypoglycemic dose) at 2.50 IU/kg of body weight incremented the Bmax by 40.53% in the HL chicks compared to saline group whereas no significant differences were observed between individuals in the LL subpopulation. Additionally, insulin increased the Bmax (23.48%) in the HL group with respect to the LL ones, indicating that the insulin responses were different according to the anxiety of each category. Epinephrine administration (0.25 and 0.50 mg/kg) incremented the Bmax in non-stressed chicks, in the LL group by about 37% and 33%, respectively, compared to ones injected with saline. In the stressed chicks, 0.25 mg/kg bw epinephrine increased the Bmax significantly in the HL group by about 24% compared to saline, suggesting that the effect of epinephrine was only observed in the HL group under acute stress conditions. Similarly, the same epinephrine doses co-administered with insulin increased the receptor density in both subpopulations and also showed that the highest dose of epinephrine did not further increase the maximum density of GABAAR in HL chicks. These results suggest that systemic epinephrine, perhaps by evoking central norepinephrine release, modulated the increase in the forebrain GABAA receptor recruitment induced by both insulin and stress in different ways depending on the subpopulation fearfulness.